ICT Equipment Investment and Growth in Low- and Lower-Middle-Income Countries - Haacker, Markus (Washington, D.C. : International Monetary Fund, 2010)
While production of ICT equipment plays a subordinate role for economic growth in most of these countries, they do benefit from capital deepening arising from falling prices of ICT equipment. Adapting established growth accounting approaches to the data environment of low-income countries, we quantify the growth impacts of absorption of ICT equipment, finding that ICT-related capital deepening contributed 0.2 percentage points to growth in low-income countries, and 0.3 percentage points in low-middle-income countries. The latter is about half the level typically found for industrialized countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet